Suicide in Nazi Germany: Transformative Family History. Issue 1 (2nd January 2023) - Messer, Jane
ABSTRACT: This article focuses on two lesser-known characteristics of German Jewish life during the Third Reich: the high rate of suicide amongst Jews and the extraordinary impediments to their migration. Beginning with memoir-narrative which centres on my Jewish father's revelation that my grandmother and great-grandmother had committed suicide, the paper then outlines the reasons for and characteristics of suicide in Nazi Germany, and the phenomenon's connection to the difficulties most Jews faced in attempting to leave Germany. I demonstrate the ways in which I have been able to reshape the family narratives told to me through historical and genealogical research, returning the given knowledge back. Researching these family and national tragedies have brought about new knowledge and transformative understandings.